Effectiveness Of Activated Carbon From Coconut Shell Through Potassium Hydroxide - Ilham Mufandi; Siti Jamilatun; Dwi Astri Ayu Purnama; Riska Utami Melani Putri (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2020)
The aim of this work is to synthesis of activated carbon from pyrolysis of coconut shell through 2 N potassium hydroxide (KOH). Carbon can be produced from material through heating at high temperatures with a porous solid containing 85%-95%. During the heating process, the carbon is only carbonized, and without oxidized in the heating chamber to avoid air leakage. Activated carbon can be used as an adsorbent. The absorption capacity of activated carbon is determined by the surface area of the particles. The absorption ability of activated carbon can be improved through an activation with chemicals such as KOH. Carbon will change in physical and chemical properties. This research used the pyrolysis process at an operating temperature of 550 °C. There were three stages of active carbon production by activating KOH, namely 1) immersion of coconut shell through 2 N KOH with a variable time of 5 days, 2) drying process of coconut shell in sunlight, 3) the burning process of dry coconut shell with the temperature of 500°C, and 4) the KOH activation process by reabsorbing activated carbon using KOH and drying in the sun. The results indicated that the water content of activated carbon was affected by drying time. The testing of the activated carbon water content shows that the quality of activated carbon meets Indonesian Standards (SNI, 1995), which is less than 15%. According to Indonesian Industrial Standard (SII) No.0258-79, the ash content of activated carbon is 2.5%, While the result in this study is exceeded 2.5%.